Optimasi Parameter 3D Printing Tipe FDM Terhadap Akurasi Dimensi dengan Filamen Berbahan Daur Ulang Plastik HDPE - Herda Agus Pamasaria; Tri Hannanto Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
One step to overcome the amount of plastic waste is to process the plastic waste into a filament for the FDM 3D Printer, but research needs to be done to get the optimum parameters to print a product with the best dimensional accuracy as the result of 3D Printing process using recycled plastic materials filament. Methods used in this research are combination of Taguchi method and PCR-TOPSIS, and the fixed parameters used in this research are layer thickness, extrusion temperature and printing speed. The purpose of selecting these parameters is to facilitate the setting process of FDM type 3D printing. The material used is a filament made from HDPE plastic recycled material. The results of this research indicate that the optimum parameter is a combination of printing temperature 260oC, layer height 0.12 mm and printing speed 50 mm/s. The most influential parameters are sorted into layer height, printing temperature and the last is printing speed.